Total Quality Management Planning Model to Increase Higher Education Performance and Competitiveness - Sutanto, Aftoni; ., Widodo; Bidayati, Utik (International Journal of Engineering and Technology, 2018)
Improving higher education performance increases competitiveness and customer satisfaction. The purpose of this research is to design a Total Quality Management (TQM) planning model to increase higher education performance and competitiveness. The focus of this research are the formulation of strategic planning for the implementation of TQM, the formulation of the operational planning, the application of the quality management, and the system of quality control in private higher education. The results of this this research is demonstrates that a national standard and a quality assurance system for higher education are used as the basis for the formulation of a quality management strategy. The formulation of TQM planning model was directed by ISO 9001 instrument, the accreditation form of The National Accreditation Board for Higher Education, and The Independent Accreditation Institution. The significant components in the implementation of TQM planning model are: a quality assurance instrument and the implementation of quality management actors, an understanding of quality management by all parties in higher education, benchmarking, education and training in quality management, leadership, reward and punishment, evaluation process, and an Integrated Management Information System. There are two roles quality control systems in private HE. These are: internal and external quality control.Â Â